Suicide attempts and markers of immune response in individuals with serious mental illness. (April 2017) - Dickerson, Faith; Wilcox, Holly C.; Adamos, Maria; Katsafanas, Emily; Khushalani, Sunil; Origoni, Andrea; Savage, Christina; Schweinfurth, Lucy; Stallings, Cassie; Sweeney, Kevin; Yolken, Robert
Abstract: Previous studies have identified elevations in antibodies to Toxoplasma gondii in individuals with a history of suicide attempts but studies have not measured the association between suicide attempts and a panel of antibody markers. We assessed 162 patients receiving treatment for schizophrenia, bipolar disorder, or major depression on the Columbia Suicide Severity Rating Scale for suicide attempt history and other clinical measures. All participants had a blood sample drawn from which were measured antibodies to Toxoplasma gondii and other neurotropic infectious agents. A total of 72 (44%) of participants had a lifetime suicide attempt; these individuals had elevated levels of IgM class antibodies to Toxoplasma gondii and Cytomegalovirus (CMV). We also found an association between the levels of these antibodies and the number of suicide attempts. There was a particularly strong odds of a suicide attempt history in individuals who had elevated levels of IgM antibodies to both Toxoplasma gondii and to CMV suggesting an additive risk associated with the antibodies. These findings remained significant when adjusting for current cigarette smoking and history of drug/alcohol use which were also associated with suicide attempts. We did not find an association between a suicide attempt history and IgG class antibodies to Toxoplasma gondii, CMV, or IgM or IgG antibodies to the Epstein Barr Virus or other antigens tested. The identification of blood-based antibody markers should provide for more personalized methods for the assessment and treatment, and ultimately prevention, of suicide attempts in individuals with serious mental illnesses.